Pelatihan Metode Pembelajaran Bahasa Jawa Krama untuk Usia Dini Bagi Guru RA dan MI - Dwiana Asih Wiranti; Muhammad Misbahul Munir (Universitas Islam Nahdlatul Ulama Jepara, 2019)
Javanese language is very important to students learn since early childhood. Where through Javanese language children can understand the positive value in the self-character. While learning Javanese etiquette in RA Miftahul Ulum and MI Miftahul Ulum 02 is still not optimal. So it is necessary to conduct training for teachers in RA Miftahul Ulum and MI Miftahul Ulum 02 in the lower classes related to the method of learning Javanese etiquette. Through this activity, the team provided training with demonstration methods about interesting learning methods, interactive and can be used to teach Javanese language especially “Krama” to early childhood. In this case early childhood is a low grade RA and MI student and training is given to teachers in RA Miftahul Ulum and MI Miftahul Ulum 02 in the lower class. This service activity has several stages which include, briefing and direction, implementation, monitoring, and evaluation. The results of this training received good appreciation from the partners. Partners actively participate in training activities. In addition, through practical activities, participants can practice the learning methods provided, so that participants are able to provide problems solving in the difficulties experienced by teachers in learning Javanese language for early childhood